2015
DOI: 10.1016/j.ssci.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations on the use and design of risk matrices

Abstract: Risk matrices are widely used in risk management. They are a regular feature in various risk management standards and guidelines and are also used as formal corporate risk acceptance criteria. It is only recently, however, that scientific publications have appeared that discuss the weaknesses of the risk matrix. The objective of this paper is to explore these weaknesses, and provide recommendations for the use and design of risk matrices. The paper reviews the few relevant publications and adds some observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
224
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(230 citation statements)
references
References 13 publications
3
224
0
3
Order By: Relevance
“…Risk matrix is a useful tool when defining the risk categories and it provides a certain selection of risks which require most immediate action (ICAO, 2009). When evaluating weaknesses and strengths of risk matrices, it can be concluded that they can be a valuable tool for identifying the critical risks (Dujim, 2015). Severity of each particular risk will be measured by using the risk classification scheme as shown in table 1.…”
Section: Fig 1 Root Causes Of Visible and Hidden Risks Presented VImentioning
confidence: 99%
“…Risk matrix is a useful tool when defining the risk categories and it provides a certain selection of risks which require most immediate action (ICAO, 2009). When evaluating weaknesses and strengths of risk matrices, it can be concluded that they can be a valuable tool for identifying the critical risks (Dujim, 2015). Severity of each particular risk will be measured by using the risk classification scheme as shown in table 1.…”
Section: Fig 1 Root Causes Of Visible and Hidden Risks Presented VImentioning
confidence: 99%
“…In the lack of reliable historical data, the estimation of probability and severity of an occurrence is initially performed by a person. Although guidance to limit the effect of biases exists (e.g., Cooke, and Goossens, 2000), the existence of biases was acknowledged by several companies and literature (Duijm, 2015;Hubbard et al, 2010;.…”
Section: How Do the Companies Perform Their Risk Management?mentioning
confidence: 99%
“…ISO 31010 (2009) recommends that a matrix should be designed to be appropriate for the circumstances. The architecture of these matrices also contains flaws (e.g., not even distribution of risk levels in the matrix) (Gauthier et al, 2012;Duijm, 2015).…”
Section: Introductionmentioning
confidence: 99%